Use of Antibiotics among Non-Medical Undergraduate Students in a Nigerian University. (2013)
Background: Antibiotic misuse is a major contributory factor to treatment failure, antibiotic resistance and high healthcare costs. Objectives: To evaluate level of self-reported antibiotic misuse among non-medical undergraduate students of a Nigerian university. Methods: Respondents’ knowledge of antibiotics and disposal system for left-over antibiotics were explored using a structured questionnaire. Data were summarized with descriptive statistics. Chi square was used to evaluate relationship between specific categorical variables and respondents’ opinions with p<0.05. Results: More than half the respondents obtained their antibiotics through doctor’s prescriptions (273;68.3%). The study revealed gross antibiotic misuse with majority, (298;74.5%) either by keeping left-over antibiotics for future use or throwing it away with refuse. Respondents (289; 72.3%) sometimes forgot to take the antibiotics. Financial constraints (73; 18.3%), long duration of treatment (70; 17.5%), side effects experienced (60;15.0%), polypharmacy (56;14.0%), tablet size (45;11.3%), and perceived low level of confidence in the prescriber (11; 2.8%) were major reasons for non-adherence. Course of study of respondents had no significant effect on respondents’ knowledge or adherence (p>0.05). Conclusion: Misuse of antibiotics among non-medical undergraduate students in a Nigerian university setting is pervasive suggesting an urgent need for enlightenment on rational use and disposal of antibiotics.